2013
DOI: 10.1371/journal.pone.0075671
|View full text |Cite
|
Sign up to set email alerts
|

Best of Both Worlds: Simultaneous High-Light and Shade-Tolerance Adaptations within Individual Leaves of the Living Stone Lithops aucampiae

Abstract: “Living stones” (Lithops spp.) display some of the most extreme morphological and physiological adaptations in the plant kingdom to tolerate the xeric environments in which they grow. The physiological mechanisms that optimise the photosynthetic processes of Lithops spp. while minimising transpirational water loss in both above- and below-ground tissues remain unclear. Our experiments have shown unique simultaneous high-light and shade-tolerant adaptations within individual leaves of Lithops aucampiae. Leaf wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Leaf photosynthetic rate is related to chlorophyll content ( Shao et al, 2014 ). Chl a is essential for determining photosynthesis, and Chl b determine the wavelengths of light that can be absorbed by the organism ( Field et al, 2013 ). Intercropped soybean leaf contained more chl a and chl b content per weight and had lower chl a/b than those in monocropping, which could broaden the wavelengths of light that could be absorbed, and effectively increase the ability of light capture ( Gong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf photosynthetic rate is related to chlorophyll content ( Shao et al, 2014 ). Chl a is essential for determining photosynthesis, and Chl b determine the wavelengths of light that can be absorbed by the organism ( Field et al, 2013 ). Intercropped soybean leaf contained more chl a and chl b content per weight and had lower chl a/b than those in monocropping, which could broaden the wavelengths of light that could be absorbed, and effectively increase the ability of light capture ( Gong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Species with large windows thrive in cloudy, high-rainfall regions, whereas species thriving in high solar irradiance regions have small windows, minimizing the probability of photo-inhibition [ 52 ]. Moreover, Lithops plants have sufficient biochemical flexibility to respond to variable light conditions within the same leaf (extreme high light intensity in the above ground region and moderate or low intensity in the below ground) [ 58 , 59 ].…”
Section: Superficial Structural Elements and Light Interceptionmentioning
confidence: 99%
“…Microscopic observations confirmed that the spatial distribution of the CaCIs is compatible with their proposed optical function [ 94 ]. Moreover, CaOx crystals within the epidermis of Lithops aucampiae leaves may scatter light within the below-ground region of the leaves, thus enriching the lower tissues with photons [ 59 ]. It was also proposed that in some species thriving in extreme environments, crystal sand may provide protection against photo-inhibition by filtering and dispersing the solar irradiance and moderating the internal leaf temperature [ 104 ].…”
Section: Mesophyll Structural Elements Allow Efficient Light Propagation and Internal Light Homogenizationmentioning
confidence: 99%
“…(b) Lithops olivacea with green bodies and large pinkish translucent windows through which sunlight penetrate into the leaf. [9] (c) Fenestrated Haworthia and Lithops with translucent tissues. [89] (d) Optical images of red laser light guided in (left) in a corn root and (right) in an oat seedling.…”
Section: Figurementioning
confidence: 99%
“…This arrangement ensures high photosynthesis yield while avoiding localized absorption at the top of the leaves, which can cause photothermal damage during hot, dry days. [9]…”
Section: Introductionmentioning
confidence: 99%